2022
DOI: 10.1111/ijfs.15771
|View full text |Cite
|
Sign up to set email alerts
|

Effects of four multi‐compound freezing medium on the quality of red drum (Sciaenops ocellatus) during frozen storage

Abstract: Taking air freezing (AF) as the reference, the effects of four types of multi-compound freezing medium for cryogenic liquid quick-freezing (immersion freezing, IF) on the freezing rate, quality and myofibrillar protein (MP) denaturation of red drum (Sciaenops ocellatus) fillets during frozen storage (À18°C) from days 0 to 90 were studied. Samples were gathered on days 0, 15, 30, 45, 60 and 90 for analysis. The results showed that IF groups (IF-1: 20% ethanol, 30% propylene glycol, 10% sodium chloride aqueous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The size of ice crystals plays a significant role in the rate of thawing. Samples from snap freezing treatment have smaller ice crystals than those treated at −70 °C and −20 °C (Zhang et al ., 2022; Zhao et al ., 2022). Smaller ice crystals thaw faster, which reduces the overall thawing time.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The size of ice crystals plays a significant role in the rate of thawing. Samples from snap freezing treatment have smaller ice crystals than those treated at −70 °C and −20 °C (Zhang et al ., 2022; Zhao et al ., 2022). Smaller ice crystals thaw faster, which reduces the overall thawing time.…”
Section: Resultsmentioning
confidence: 99%
“…Smaller ice crystals thaw faster, which reduces the overall thawing time. Similar studies have reported the effect of the freezing method on thawing rate and time (Zhang et al ., 2022; Zhao et al ., et al ., 2022). The fastest thawing time and highest thawing rate were observed in the snap freezing method with ohmic thawing and double‐sided IR pre‐treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The decrease in Ca 2+ ‐ATPase activity is related to the irregular aggregation and rearrangement of myosin heads induced by the unfolding of myosin conformational sites (Fig. 2) (Zhao et al ., 2022). Meanwhile, the irregular aggregation of Mfp accompanied the production of carbonyl groups, resulting in the reduction of sulfhydryl groups and a subsequent decline in Mfp gel‐forming capacity, thus producing an adverse influence on the texture, flavour and sensory attributes of the final product (Nikoo et al ., 2019; Jing et al ., 2022).…”
Section: Resultsmentioning
confidence: 99%